2019
DOI: 10.1016/j.ajoc.2019.100499
|View full text |Cite
|
Sign up to set email alerts
|

High fluence PACK-CXL as adjuvant treatment for advanced Acanthamoeba keratitis

Abstract: Purpose To describe the outcome of adjuvant high fluence photoactivated chromophore for infectious keratitis cross-linking (PACK-CXL) used to treat an advanced form of refractory Acanthamoeba keratitis (AK) diagnosed several months after initial presentation. Observations An otherwise healthy 24-year old female presented with a severe unilateral keratitis. The diagnosis eluded clinicians for several months and when finally confirmed as AK, anti-amoebic therapy was insta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 32 publications
(37 reference statements)
0
7
0
Order By: Relevance
“…The results showed that in bacterial or fungal keratitis, PACK-CXL may be a useful adjunct therapy for reducing the time to complete corneal healing, but PACK-CXL was not useful compared to SAT alone in reducing the infiltrate size, improving visual acuity, or reducing the risk of adverse effects, such as the worsening of infectious keratitis, corneal melt, or perforations [ 46 ]. The microbicidal effect of PACK-CXL likely arises from ultraviolet A (UVA) induced DNA damage and reactive oxygen species release [ 15 , 47 , 48 ], while pain reduction may be secondary to the suppression of inflammation and nociception by subepithelial nerves [ 47 ]. PACK-CXL has been used along with standard antimicrobial therapy to treat persistent cases of Acanthamoeba spp.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that in bacterial or fungal keratitis, PACK-CXL may be a useful adjunct therapy for reducing the time to complete corneal healing, but PACK-CXL was not useful compared to SAT alone in reducing the infiltrate size, improving visual acuity, or reducing the risk of adverse effects, such as the worsening of infectious keratitis, corneal melt, or perforations [ 46 ]. The microbicidal effect of PACK-CXL likely arises from ultraviolet A (UVA) induced DNA damage and reactive oxygen species release [ 15 , 47 , 48 ], while pain reduction may be secondary to the suppression of inflammation and nociception by subepithelial nerves [ 47 ]. PACK-CXL has been used along with standard antimicrobial therapy to treat persistent cases of Acanthamoeba spp.…”
Section: Resultsmentioning
confidence: 99%
“…PACK-CXL has been used along with standard antimicrobial therapy to treat persistent cases of Acanthamoeba spp. infection [ 47 ]; however, there is currently insufficient evidence to support its use in the setting of AK [ 46 , 49 , 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…Nateghi Petterson et al [54] performed accelerated PACK-CXL with higher total fluence (7.2 J/cm 2 ) in a case refractive to pharmacology and a previous PACK-CXL procedure (5.6 J/cm 2 ) [54]. This was effective despite the discontinuation of antiprotozoal drugs due to potential negative side effects on epithelial wound healing.…”
Section: Acanthamoeba Keratitismentioning
confidence: 99%
“…There is limited evidence for the use of PACK-CXL against Acanthamoeba keratitis. Laboratory models [69,70,97] of the effects of PACK-CXL on Acanthamoeba keratitis have shown poorer results than the outcomes of clinical cases [52,54,74,98]. This may be due to several reasons, such as difficulty in exposing their Acanthamoeba samples to antiprotozoal medication in a similar way, lack of culture and/or treatment media analogous to the human cornea, assessing effectiveness through requiring rapid eradication, or infecting corneae with protozoal numbers over typical, acute keratitis.…”
Section: Acanthamoeba Keratitismentioning
confidence: 99%
“…PACK-CXL is an area of ongoing research and development. Higher UV fluences [79,80,81 ▪ ], and the use of alternative chromophore and light wavelength combinations, such as rose bengal/532 nm green light are being investigated as potentially more effective treatments of infectious keratitis of bacterial, fungal or parasitic origin [82–85], although further investigation and optimization are necessary before widespread clinical implementation can occur.…”
Section: High-fluence Eramentioning
confidence: 99%